ANALISIS KETERAMPILAN MENYIMAK DALAM PEMBELAJARAN BAHASA INDONESIA MELALUI MEDIA MOTION GRAPHIC - Vita Alfiatul Safitri; Afakhrul Masub Bakhtiar (STKIP Subang, 2022)
Listening skill are skills that has an important role in students' academic success. The purpose of this study was to analyze the skills of listening to fiction stories in Indonesian language learning through motion graphic media in grade IV A MI Miftahul Ulum Gresik students. Researchers are interested in the barriers to students' listening skills. This study uses descriptive qualitative research methods that aim to describe the events that occurred during the research process. The subjects of this study were students of class IV A MI Miftahul Ulum Gresik, totaling 28 students, as long as the data were taken from observations, tests, and interviews. The results showed that the listening skills of class IV A MI Miftahul Ulum Gresik students were quite good when using learning media in the form of motion graphic videos. This can be seen from each indicator of listening skills. There are several indicators of listening that are presented, namely listening, paying attention, understanding and responding. Efforts are being made to improve students' listening skills by updating strategies, learning methods, and using creative and innovative learning media. As a teacher, it is also necessary to provide special guidance for students who are less active in listening learning.